Manure utilisation, drought cycles and herd dynamics in the Sahel: implications for cropland productivity - Williams, Timothy O.; Powell, J.M.; Fernández Rivera, S. (International Livestock Centre for Africa, 1995)
Animal manure is of vital importance to soil-fertility maintenance in semi-arid West Africa due to its intrinsic value as a soil amendment and because of the low level of inorganic fertiliser use. This paper provides a regional overview of manure utilisation for food crop production. Results of experimental trials and on-farm studies are reviewed to evaluate the agronomic and economic effectiveness of livestock manure as a source of nutrients for millet and sorghum production. The potential and actual amounts of manure available for crop production during normal rainfall years are estimated, and the effect of drought-induced changes in livestock population and species composition on manure availability and cropland productivity are assessed. In doing this, on-station and on-farm data from Niger are used to assess nutrient losses from croplands and to estimate the amount of manure required to maintain crop production at various yield levels. The number of animals needed to produce this level of manure and the feed resources required to maintain them are estimated and compared with the level of livestock holdings and feeds found in village studies. The influence of drought on the structure of national and village herds are evaluated and the amounts of different types of manure that are likely to be available in the years immediately preceding and following a drought are estimated. These estimates and feed availability parameters are used to assess the adequacy of available manure for food crop production, and the role that manure and other soil amendments can play in the future intensification of agricultural production in semi-arid West Africa.